Maranao-Muslim Food Culture in Quiapo: Reimagining the Role of Food and Commensality in Interreligious Understanding in Manila - Tallara, Marik Iñigo M. (Archīum Ateneo, 2024)
Quiapo is a well-known Catholic pilgrimage site to honor the Black Nazarene. Unknown to many Filipinos, Quiapo, a district of Manila, is also a hub for Muslim culture. While the Muslim population in the Philippines was afflicted by a history of conflict and violence, what is remarkable in Quiapo is how Muslims and Catholics have come together to establish bonds of friendship over food. During the festival of the Black Nazarene, Catholics share food with everyone including Muslims. At the same time, Muslims participate in this festival through sharing space and peddling halal food to the Catholic participants. This ethnohistorical study focuses on the Maranao-Muslim community and their food culture. It examines how the association of people to food can advance interreligious understanding. Moreover, it explores the Pagana, a banquet showcasing the traditional Maranao recipes and how it can be reenacted or replicated to understand the connection of food in a reimagined space where people are sitting down and eating together. The discussion hopes to show how food and commensality can be a medium to mitigate differences and tensions and create spaces for peace and harmony. This analytical step is consistent with the presupposition of this study, that food culture is an alternative framework in interreligious study and policy-making process in the Philippines.